The Influence of Perceived Quality to Purchase Decision: Study in Serum Implora Cosmetics Product in Kabupaten Bandung Barat - Ayu Puspita Dewi; Ivon Sandya Sari Putri (Universitas muhammadiyah malang, 2023)
Along with the habits of the Indonesian people to perform skin care, local products for beauty and body care products are emerging on the market. Implora is a local product brand which in 2021 launched their first skincare product, serum. In March 2022, Implora was named the best-selling serum product in e-commerce, but a few months later the product sales volume decreased due to negative reviews regarding the Implora serum. This study aims to determine how the influence of perceived quality on purchasing decisions. This research uses a quantitative approach, with an explanatory survey method. The sample was determined using the non-probability sampling method, with the acquisition cost using purposive sampling, namely respondents who know and have used Implora serum with a total sample of 155 respondents. This research uses a simple linear regression method. The results of this study indicate that there is a positive and significant influence of the perceived quality variable on the purchasing decision variable. It was also found that the effect of the quality perception variable was 36% on purchasing decisions. The results of this study can be used by industry players to increase sales volume again. For further research, other independent variables can be added because there are other factors that influence purchasing decisions besides perceived quality.